1991
DOI: 10.1079/bjn19910066
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tea on iron and aluminium metabolism in the rat

Abstract: Weanling male Wistar rats were fed for 28 d on a semi-synthetic diet containing normal (38 pg/g) or low (9 pg/g) levels of iron. They were given water or tea infusion (20 g leaves/l water) to drink. Two further groups were given a normal-or low-Fe diet containing added tea leaves (20 g/kg diet). At the end of the study period, all rats given the low-Fe diet were severely anaemic, as assessed by haemoglohin, packed cell volume and liver Fe. Those given tea or the diet with added tea leaves showed a greater degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Reports of CT complexes with other cations are scarce and usually related to tea consumption. Tea tannins have been reported to inhibit Al absorption in humans and rats (Fairweather-Tait et al, 1991), but was found to have no effect in other studies (Greger and Lyle, 1988).…”
Section: The Interactions Between Minerals and Condensed Tanninsmentioning
confidence: 98%
“…Reports of CT complexes with other cations are scarce and usually related to tea consumption. Tea tannins have been reported to inhibit Al absorption in humans and rats (Fairweather-Tait et al, 1991), but was found to have no effect in other studies (Greger and Lyle, 1988).…”
Section: The Interactions Between Minerals and Condensed Tanninsmentioning
confidence: 98%
“…Although some work has suggested that the absorption of A1 after tea drinking is increased (Koch et al 1988), this measured total A1 in 24 h urine and did not take into account the diuretic effect of tea, nor has it been supported in studies with rats (Fairweather-Tait et al 1991). Tea inhibits the absorption of non-haem-Fe from the diet (Disler et al 1975;Fairweather-Tait et al 1991) and it is possible that a similar inhibitory effect on absorption of A1 from other dietary sources is seen when food is taken with tea.…”
Section: Other Ligandsmentioning
confidence: 99%
“…Some scholars believe that iron deficiency in the body is significantly associated with iron content in tissues. The iron concentration in the liver and spleen is usually higher than other tissues (Fischer et al, 2002), so it is often used to evaluate the iron status of the body (Fairweather-Tait, Piper, Fatemi, & Moore, 1991;Fischer et al, 2002;Park, Bacon, Brittenham, & Tavill, 1987;Whittaker et al, 1997). There was no significant difference in iron content between the iron supplement groups in the kidneys and liver of the mice, probably due to the faster catabolism of iron in the liver and kidneys.…”
Section: Weight Change and Tissue Iron Contentmentioning
confidence: 99%